Volume 3: Heat Transfer, Parts a and B 2009
DOI: 10.1115/gt2009-60047
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Slot Injection, Effusion Array and Dilution Hole on the Cooling Performance of a Real Combustor Liner

Abstract: Due to the higher cooling requirements of novel combustor liners a comprehensive understanding of the phenomena concerning the interaction of hot gases with different coolant flows plays a major role in the definition of a well performing liner. An experimental analysis of a real engine cooling scheme was performed on a test article replicating a slot injection and an effusion array with a central large dilution hole. Test section consists of a rectangular cross-section duct and a flat perforated plate with 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Ceccherini et al [12] conducted studies on the combined effect of a slot injection, comparable to a starter film, effusion array and dilution hole on the cooling performance of a combustor liner. An increasing blowing ratio leads to a decrease in cooling effectiveness due to penetration of cooling air into the main flow.…”
Section: Related Past Investigationsmentioning
confidence: 99%
“…Ceccherini et al [12] conducted studies on the combined effect of a slot injection, comparable to a starter film, effusion array and dilution hole on the cooling performance of a combustor liner. An increasing blowing ratio leads to a decrease in cooling effectiveness due to penetration of cooling air into the main flow.…”
Section: Related Past Investigationsmentioning
confidence: 99%
“…An interesting attempt to characterize the effects of the swirled flow on combustor heat transfer is conducted by Patil et al [11] which, studying an air spray nozzle with a swirl number of 0.7, pointed out how increasing Reynolds number does not change the position of the peak in heat flux due to the impingement of the swirl flow on the liner, whereas the intensity of the peak is reduced. However, as already mentioned, most studies devoted to effusion cooling deal with flat plates which have been quite exten sively studied both singularly and with additional cooling features such as impingement jets [12,13], slot cooling [14], and dilution holes [15,16]. Focusing on effusion systems only, Behrendt et al [4] showed that shallow angles promote cooling effectiveness due to reduced jet penetration and increased heat removal within the perforations.…”
Section: Introductionmentioning
confidence: 97%
“…In the following rows the effectiveness slightly decreases due to the wake of the dilution jet, and finally reaches an asymptotic value at the end of the plate. The presence of the slot coolant strongly enhances the adiabatic effectiveness: according to Andreini et al [9], after the first three rows, where the η aw remains nearly constant, there is a lower effectiveness area due to the interaction of the slot coolant and the effusion jets; after the dilution hole, η aw reaches an asymptotic value. Finally Figure 9 shows the averaged adiabatic effectiveness results for the whole test matrix, plotted versus BR e f f and V R e f f .…”
Section: Heat Transfer Coefficientmentioning
confidence: 99%
“…T aw was evaluated through a post-processing procedure which takes into account the thermal fluxes across the plate due to conduction and due to the coolant inside the annulus and the holes. This procedure is based on a 1D approach and considers the following equation: (9) where T w is the wall temperature measured with TLC. Heat flux across the plate (q) is evaluated through TLC wall temperature, coolant temperature and using the Colburn correlation Nu = 0.023Re 0.8 Pr 1/3 to estimate heat transfer coefficients inside the holes and on the annulus side of the plate; Reynolds and Nusselt numbers were evaluated with the hole diameter and with the annulus cross section hydraulic diameter respectively.…”
Section: Effectiveness Measurementsmentioning
confidence: 99%
See 1 more Smart Citation